The history of climate and society: a review of the influence of climate change on the human past. (1st October 2022) - Degroot, Dagomar; Anchukaitis, Kevin J; Tierney, Jessica E; Riede, Felix; Manica, Andrea; Moesswilde, Emma; Gauthier, Nicolas
Abstract: Recent decades have seen the rapid expansion of scholarship that identifies societal responses to past climatic fluctuations. This fast-changing scholarship, which was recently synthesized as the History of Climate and Society (HCS), is today undertaken primary by archaeologists, economists, geneticists, geographers, and paleoclimatologists. This review is the first to consider how scholars in all of these disciplines approach HCS studies. It begins by explaining how climatic changes and anomalies are reconstructed by paleoclimatologists and historical climatologists. It then provides a broad overview of major changes and anomalies over the 300, 000-year history of Homo sapiens, explaining both the causes and environmental consequences of these fluctuations. Next, it introduces the sources, methods, and models employed by scholars in major HCS disciplines. It continues by describing the debates, themes, and findings of HCS scholarship in its major disciplines, and then outlines the potential of transdisciplinary, 'consilient' approaches to the field. It concludes by explaining how HCS studies can inform policy and activism that confronts anthropogenic global warming.